2020
DOI: 10.37256/amtt.112020132
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Virulence-Modulating Effects of Thyme Essential Oil against Fusarium spp., Causing Wheat Diseases

Abstract: Wheat (Triticum aestivum L.) is one of the important cereals and a major source of human food worldwide. Fusarium pseudograminearum and F. culmorum are the causal agents of important diseases on wheat, including head scab, crown and root rot. Control of Fusarium diseases on wheat is very difficult and important because of not only no complete resistance in any wheat cultivar and long-term survival of the soil-borne pathogen, but also production of carcinogenic mycotoxins in wheat tissues, which are harmful for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In the part of the experiment regarding the influence of essential oils on the development of mycelium of pathogens of the Fusarium genus, it was assessed that in most tested combinations in which thyme essential oil was used, the growth of the discussed fungi was completely inhibited. In a study conducted by Faghih-Imani et al [69], it was found that the use of thyme EO contributes to the inhibition of the mycelium growth of pathogens of the Fusarium genus as well as their germination and spore production. Palfi et al [70] assessed the effect of different essential oils on the growth of Fusarium oxysporum mycelium.…”
Section: Discussionmentioning
confidence: 99%
“…In the part of the experiment regarding the influence of essential oils on the development of mycelium of pathogens of the Fusarium genus, it was assessed that in most tested combinations in which thyme essential oil was used, the growth of the discussed fungi was completely inhibited. In a study conducted by Faghih-Imani et al [69], it was found that the use of thyme EO contributes to the inhibition of the mycelium growth of pathogens of the Fusarium genus as well as their germination and spore production. Palfi et al [70] assessed the effect of different essential oils on the growth of Fusarium oxysporum mycelium.…”
Section: Discussionmentioning
confidence: 99%